2011
DOI: 10.1097/gme.0b013e3181ec58f8
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and affective anxiety symptoms and menopausal hot flashes

Abstract: These results suggest that the positive association between higher ZAI scores and hot flashes in recently postmenopausal women may be due to the overlap between the somatic manifestation of hot flashes and anxiety symptoms rather than to an affective anxiety disturbance. These results have potential implications for the care and treatment of postmenopausal women, but replication is required in other samples including women at different transition stages of menopause and women with psychiatric comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Anxiety symptoms have been identified as a strong risk factor for hot flashes, 8, 10, 21, 2830 but it is not known whether anxiety amplifies or is primarily a predictor of hot flashes. 31 It has also been suggested that the association between anxiety symptoms and hot flashes is due to an overlap of somatic symptoms of both disorders rather than to the psychological condition of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety symptoms have been identified as a strong risk factor for hot flashes, 8, 10, 21, 2830 but it is not known whether anxiety amplifies or is primarily a predictor of hot flashes. 31 It has also been suggested that the association between anxiety symptoms and hot flashes is due to an overlap of somatic symptoms of both disorders rather than to the psychological condition of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…31 It has also been suggested that the association between anxiety symptoms and hot flashes is due to an overlap of somatic symptoms of both disorders rather than to the psychological condition of anxiety. 30 Both anxiety and hot flashes have physiologic and psychological components that are difficult to disentangle, and whether anxiety is associated with responses to hot flash treatments is also not known. Increased understanding of the role of anxiety in hot flashes might lead to treatments that reduce both anxiety and hot flashes, but further studies that evaluate these issues are needed.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized an effect modification of menopausal stage on dimensions of somatic and affective anxiety, with increased associations in the menopause transition. Based on evidence in previous studies, 8,11 we also hypothesized that somatic anxiety was an independent risk factor of menopausal hot flashes.…”
Section: Introductionmentioning
confidence: 98%
“…714 Conflicting findings are in part due to the varied manifestations of anxiety syndromes and disorders and to the nature of the somatic symptoms of anxiety, which are similar to somatic complaints of hot flashes, and the consequent difficulty of disentangling the two conditions. 11, 14, 15 There is also little evidence to indicate whether anxiety is a precursor or a consequence of hot flashes, and whether anxiety influences perceptions of hot flashes or augments the event of hot flashes. 12 …”
Section: Introductionmentioning
confidence: 99%
“…However, it is suggested that this association is due to the overlapping of anxiety's somatic symptoms and the hot fl ushes' physical manifestations, given that these vasomotor symptoms are connected with the somatic dimension of anxiety, but not with the affective one (Lermer et al, 2011).…”
mentioning
confidence: 99%